Challenges and Key Elements of the Educational Inspection Model in Andalusia - Barbero Alcalde, Ana María; Úbeda-Portugués Ávila, Gema (Avances en Supervisión Educativa, 2026)
Educational Inspection constitutes a key component of the education system due to its regulatory guarantee function, its technical dimension, and its contribution to improving educational quality and equity. In the current context, marked by regulatory, social, and organizational changes, the planning of inspection activity takes on a strategic role in guiding intervention priorities and responding to new systemic demands. This article focuses on the Educational Inspection model in Andalusia, taking as its reference the planning instruments that organize and regulate it, particularly the General Plan of Action 2023–2027 and its annual implementation. From a systemic perspective, the paper addresses the recent evolution of this model in relation to intervention referents, the types of actions planned, and the principles underpinning inspection activity. Likewise, the Andalusian framework is situated within the broader national debate on the role of Educational Inspection in the 21st century, considering its functions of supervision, evaluation, guidance, and reporting. The text, therefore, aims to provide a well-founded overview of the design and orientation of inspection planning in Andalusia, as a starting point for reflecting on its alignment with current challenges facing the education system and with the purposes attributed to Educational Inspection by current legislation.
Keywords: Educational Inspection, Andalusia, planning, evaluation, equity, education system, training, innovation